Patient-Perceived Barriers to Accessing Cleft Care at a Tertiary Referral Center in São Paulo, Brazil. (May 2019) - Ise, Ananda; Menezes, Camila; Batista Neto, Joao; Saluja, Saurab; Amundson, Julia R.; Jenny, Hillary; Massenburg, Ben; Citron, Isabelle; Alonso, Nivaldo
Background: In low- and middle-income countries, poor access to care can result in delayed surgical repair of orofacial clefts leading to poor functional outcomes. Even in Brazil, an upper middle-income country with free comprehensive cleft care, delayed repair of orofacial clefts commonly occurs. This study aims to assess patient-perceived barriers to cleft care at a referral center in São Paulo. Methods: A 29-item questionnaire assessing the barriers to care was administered to 101 consecutive patients (or their guardians) undergoing orofacial cleft surgery in the Plastic Surgery Department in Hospital das Clínicas, in São Paulo, Brazil, between February 2016 and January 2017. Results: A total of 54.4% of patients had their first surgery beyond the recommended time frame of 6 months for a cleft lip or cleft lip and palate and 18 months for a cleft palate. There was a greater proportion of isolated cleft palates in the delayed group (66.7% vs 33.3%). Almost all patients had a timely diagnosis, but delays occurred from diagnosis to repair. The mean number of barriers reported for each patient was 3.8. The most frequently cited barriers related to lack of access to care include (1) lack of hospitals available to perform the surgery (54%) and (2) lack of availability of doctors (51%). Conclusion: Delays from diagnosis to treatment result in patients receiving delayed primary repairs. The commonest patient-perceived barriers are related to a lack of access to cleft care, which may represent a lack of awareness of available services.